Morphological Characteristics and Genetic Relationship of Red Snappers (Lutjanus timoriensis, Lutjanus malabaricus, Lutjanus erythropterus) in Papuan Waters - Pranata, Bayu; Sala, Ridwan; Kusuma, Aradea Bujana; Purbani, Debora Christin; Mokodongan, Daniel Frikli; Sipriyadi, Sipriyadi; Azhar, Muhamad Ilham (Marine Science Department Diponegoro University, 2024)
Environmental and genetic variables can exert an influence on alterations in morphological traits. Within fish species inhabiting diverse aquatic settings, there can be observed variations in morphological traits. Genetically, variations in fish morphological characteristics can occur through mating and gene flow. To date, there has been a lack of research conducted on the variability in morphological traits and genetic relationships between Lutjanus timoriensis, L. malabaricus, and L. erythropterus. Thus, the current research aimed to identify variations in the morphological characteristics as well as in the intra- and inter-specific relationships between three red snapper species from the genus Lutjanus. Cytochrome oxidase I (COI) gene was used to study the molecular relationship among species of red snapper. The results showed that L. timoriensis had high intraspecific morphological variation in young individuals. Morphologically, L. timoriensis, L. malabaricus, and L. erythropterus are very similar. Unlike L. malabaricus and L. erythropterus, young and adult L. timoriensis have black patches in the pectoral fin axils. The adult L. erythropterus has a comparatively small mouth, no hump on its head, and no black saddle at the base of its tail. Meanwhile, L. malabaricus has a comparatively large mouth, a head with a hump, and a black saddle at the base of its tail. In terms of body size, L. erythropterus is larger than L. timoriensis and L. malabaricus. Based on NCBI and Bold System data, molecular analyses determined that the observed fish were L. timoriensis, L. malabaricus, L. erythropterus with a similarity of between 99.85 and 100%. The phylogenetic tree construction demonstrated that L. malabaricus, L. timoriensis and L. erythropterus were closely related.